DYNAMIC AIRBORNE REROUTE PROGRAM (DARP) APPLICATION IN BUSINESS AVIATION (Perner's Contacts, 2014)
With relatively significant growth of business aviation oceanic operations the need to optimize them raises. With the free flight concept introduction new opportunities are now available for the operators. Dynamic Airborne Reroute Program (DARP) may be one of them. The pros and cons are analysed in this article.
Keywords: Air Transportation; Business Aviation; Free Flight; DARP